DESIGN AND CONSTRUCTION OF SEWING EQUIPMENT SALES INFORMATION SYSTEM IN NEW WEBSITE BASED GIFT SHOP - Ramadhan, Putut Pujagiri; Setyawati, Endang; Wibowo, Adhi (LPPM STMIK Dharmapala Riau, 2024)
Toko Karunia Baru is a sewing equipment shop located at ruko F number 7, Wonokriyo Gombong market, Kebumen, Central Java. In its operations, Toko Karunia Baru still uses manual methods and is not yet computerized. After knowing the problems at Toko Karunia Baru, steps to overcome these problems require an information system that can support Toko Karunia Baru's activities in running its business faster. The purpose of this study is to build a Website-Based Sewing Equipment Sales Information System Design at Toko Karunia Baru that can speed up the recapitulation of sales reports so that they are more efficient. The method used is a prototype, the results of the benefit test show that the average time before using the system is 10.34 and the average time after using the system is 01.58 minutes. With the benefit test using the McCall standard, Correctness was 94.67%, Reliability 91.33% Efficiency was 95%. Thus, it can be concluded that the Design and Construction of a Website-Based Sewing Equipment Sales Information System at the Karunia Baru Store can overcome problems in the utilization of technological facilities and efficiency in managing goods data.